When museology and museums do not reach the Peripheries and varzéa football: Case study of Sete de Setembro in Vila Progresso (Cadernos de Sociomuseologia, 2023)
Varzea football is a widespread sport in the outskirts of Brazil. In the city of São Paulo, this practice transcends sport and becomes one of the main attractions in the neighborhoods, whether due to the scarcity of leisure options or a tradition that accompanies the growth of the neighborhoods. The practice of floodplain football in the East Zone of the City of São Paulo is widespread with several traditional teams, including the Sete de Setembro. Currently, the team has a headquarters on private land, but throughout its history it has had four fields, all within the limits of Vila Progresso. This article analyzes the relationship between Clube Sete de Setembro da Vila Progresso and its neighborhood, searching for social memories around the field through interviews with people linked to the club and the neighborhood. In this way, we will understand how this relationship has influenced and still historically influences the lives of this neighborhood and these people. We will affirm that the search for these memories broadens the view of the football field beyond its usual functionality and places it as a possible space of memory.Keywords: memory, varzea football, place of memory.